Predictors of job motivation among doctors and nurses in a tertiary hospital in Sokoto, Nigeria - Kaoje, Aminu U.; Magaji, Bello A.; Raji, Mansur O.; Oladigbolu, Remi A.; Mohammed, Mansur B. K.; Sani, Mohammed; Yahya, Zakeeyu B. (International Journal Of Community Medicine And Public Health, 2019)
Background: Doctors and nurses are the largest and very important human resources for health within health service organizations; therefore their performance will impact the overall organizational performance. The study was aimed to assess the predictors of job motivation among Doctors and nurses of a tertiary hospital. Methods: A descriptive cross sectional study was conducted among 334 doctors and nurses. Multi-stage sampling method was used to select study respondents and self-administered questionnaires developed based on Maslow and Herzberg theories of motivation. Linear regression analysis was performed to determine the predictors of job motivation. The level of statistical significance was set at p<0.05. Results: The motivators were ranked in order of importance from achievement factors, remuneration, job attributes and co-workers. Linear regression revealed only respondents’ designation significantly predicted job attributes as a motivating factor. Doctors were less likely to be motivated by their job attributes compared with nurses (p=0.03). Sex (p=0.01) and holding managerial position (p=0.001) predicted remuneration as a motivating factor for doctors and nurses. Disaggregation by profession showed, only holding managerial position (p=0.02) predicted remuneration as a motivating factor for doctors while for nurses, predictors were sex (p=0.001) and holding managerial position (p=0.02). Co-workers as a motivating factor for all groups were predicted by holding managerial position (p=0.01) and designation (p=0.03). Conclusions: Motivation was influenced by both financial (remuneration) and non-financial incentives (achievements). Healthcare professionals tend to be motivated more by non-financial factors, implying that this should be a cogent strategy for effective employee management.